2009
DOI: 10.1890/08-0419.1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the evolution of reduced mycorrhizal dependence during plant invasion

Abstract: Abstract. Introduced species inevitably experience novel selection pressures in their new environments as a result of changes in mutualist and antagonist relationships. While most previous work has examined how escape from specialist enemies has influenced herbivore or pathogen resistance of exotic species, post-introduction shifts in exotic dependence on mutualists have not been considered. In a common environment, we compared dependence on AM fungi of North American and European populations of Hypericum perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
150
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(165 citation statements)
references
References 46 publications
8
150
3
1
Order By: Relevance
“…AM symbiosis increased the aboveground biomass in low P (non-fertilized) but not in high P (fertilized) pots and increased root biomass in both non-fertilized and P-fertilized treatments. Seifert et al (2009) showed that the response of H. perforatum to root colonization by AMF usually is positive, but it can strongly differ depending on the plant genotype and clone. In contrast to the present study, Zubek et al (2012) did not find any effect of the arbuscular mycorrhizal symbiosis on shoot biomass of H. perforatum, irrespective of using inocula of single or multiple AM species.…”
Section: Discussionmentioning
confidence: 99%
“…AM symbiosis increased the aboveground biomass in low P (non-fertilized) but not in high P (fertilized) pots and increased root biomass in both non-fertilized and P-fertilized treatments. Seifert et al (2009) showed that the response of H. perforatum to root colonization by AMF usually is positive, but it can strongly differ depending on the plant genotype and clone. In contrast to the present study, Zubek et al (2012) did not find any effect of the arbuscular mycorrhizal symbiosis on shoot biomass of H. perforatum, irrespective of using inocula of single or multiple AM species.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their ubiquity and location in the root-soil interface, AMF have been referred to as keystone mutualists (O'Neill et al, 1991), although parasitic interactions have been observed under controlled conditions (Johnson et al, 1997). Several invaders, such as garlic mustard (Allaria petiolata), are nonmycorrhizal, which has led to suggestions that invasive plants are either non-mycorrhizal or have a low inherent or evolved mycorrhizal dependency (van der Putten et al, 2007;Seifert et al, 2009;Vogelsang and Bever, 2009). On the other hand, AMF increase growth and competitiveness of spurge and knapweed-two of the most invasive plants in the intermountain west of the USA-under controlled conditions (Marler et al, 1999;Klironomos, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, AMF associations were found less frequent among invasive species than native species (Vogelsang et al 2004, Pringle et al 2009). Furthermore, rapid evolution of the plant's decreased reliance on AMF mutualists during invasion has been documented (Seifert et al 2009). Notwithstanding, opposite findings have also been reported.…”
Section: Introductionmentioning
confidence: 99%